PENERAPAN PEMBELAJARAN BERDIFERENSIASI BERDASARKAN KESIAPAN BELAJAR DI TINGKAT SEKOLAH MENENGAH ATAS - Anisa Umu Salamah; Anti Dhamayanti Fauzi; Daryanti Wahyu Lestari; Dian Fitriani; Asep Saefullah (Universitas Muhammadiyah Kotabumi, 2023)
Abstract: Every individual has their uniqueness and characteristics. Likewise, students were individuals who have uniqueness and characteristics that vary from one another. In class X in one of the high schools in Serang City, there is a variety of learning readiness it is necessary to do differentiated learning to meet this diversity so that students can optimize their potential according to their competence. The purpose of lessons is to determine the impact of the application of differentiated learning on the learning process and how it be apply in class X Biology subjects. This research uses descriptive qualitative type with the source of research information from students. Modificated of lesson plans and LKPD for Biology subjects based on differentiated learning based on the diversity of students' learning readiness. The results showed an impact on changes in the behavior of students who were more active and enthusiastic in Biology learning activities. Therefore, it can be conclude that the Problem-Based Learning (PBL) learning model based on differentiated learning readiness can be apply in class X.